Understanding globalization - Schirato, Tony (SAGE, 2003)
"Globalization is probably the most significant and debated term in the contemporary world: struggles over what it means are played out in a variety of ways and sites, from academia and the media to the streets of Seattle, Melbourne and Genoa. And while most analysts accept the importance of the changes (technological, economic, cultural, political) associated with the term 'globalisation', very few agree as to what these changes mean, or, if taken together, they add to something that really exists for 'everyone', either as access to technology, a world view, or simply a name and set of discourses that 'does things'." SUMMARY.